THE IMPROVEMENT OF INTERACTION TECHNOLOGY OF MINING AND METALLURGICAL COMPLEX ENTERPRISES IN THE DIRECTION OF DONBASS - KRYVBAS BY USING STRICT SCHEDULE - Papakhov, O. Yu.; Logvinova, N. O. (Science and Transport Progress, 2009)
In transportation of raw materials between the enterprises of ore mining and smelting complex on the Donbas – Kryvbas direction it is used a considerable quantity of Ukrzaliznytsya’s rolling stock and private wagons of metallurgical enterprises, which stand pending the freight operations at terminals and worsen the turnout of wagons, and decrease the productivity of using them due to an idle time pending the freight operations, considerable empty run and turnout of block trains.